A view to a kilt - Dunnett, Kaitlyn (Dunnett, Kaitlyn. Liss MacCrimmon mystery., 2020)
Liss has suddenly found herself in charge of the March Madness Mud Season Sale, a town-wide celebration created to boost the local economy during the slushy weeks of early spring. With businesses ailing after a rough winter, the pressure is on to make this year<U+2019>s effort the can<U+2019>t-miss-event of the season. But before Liss can get her hands dirty, her husband makes a horrifying discovery. There<U+2019>s a dead man on their property, and he didn't die of natural causes . . . Stunned by the murder mystery developing in her own backyard, Liss receives another shock. The victim is identified as Charlie MacCrimmon, an uncle believed to have died eleven years before Liss was born. No one has seen or heard from Charlie since he went off to fight in Vietnam. What secrets could he have been hiding for so many years, and who would want to kill a man long thought to be dead? Enlisting the help of her family, Liss uncovers more questions than answers as she delves into her uncle<U+2019>s murky past. One thing is clear<U+2014>before he met his end, Uncle Charlie was desperately trying to warn her about something sinister. And unless Liss can soon track down a maniacal criminal as elusive as the Loch Ness Monster, she just might be the next MacCrimmon to disappear . . .